Effectiveness of Ice Pack Application on Pain During Intravenous Insertion Procedures in Preschool-Aged Children - Fini Heryani; Haryatiningsih Purwandi (Indonesian Journal of Global Health Research, 2026)
Introduction: Intravenous (IV) cannulation in preschool-aged children often causes pain, which can affect their comfort and overall experience in hospital. Various pain reduction techniques, such as deep-breathing and distraction, are commonly used but are not always effective in directly minimising pain. One non-pharmacological method to reduce pain is the application of ice packs or cold compresses. Aim: This article review aims to evaluate the effect of ice pack application on pain in preschool-aged children undergoing IV cannulation. Methods: This literature review utilised five databases: Google Scholaa Intravenous (IV) cannulation in preschool-aged children often causes pain, which can affect their comfort and overall experience in hospital. Various pain reduction techniques, such as deep-breathing and distraction, are commonly used but are not always effective in directly minimising pain. One non-pharmacological method to reduce pain is the application of ice packs or cold compresses.  This article review aims to evaluate the effect of ice pack application on pain in preschool-aged children undergoing IV cannulation. This literature review utilised five databases: Google Scholar, ScienceDirect, ResearchGate, PubMed, and Portal Garuda. The keywords used included “use of ice pack in preschool children”, “effectiveness of ice compress”, and “IV cannulation”. Of the 138 articles published between 2015 and 2025 prospective articles identified, only 13 met the inclusion criteria. The quality of the articles was assessed using the 2020 CASP instrument. Based on data extraction, the authors found that the use of ice packs is effective as a non-invasive intervention and can reduce pain during IV insertion. Conclusion: Paediatric nurses are advised to consider the use of ice packs as part of atraumatic care in order to minimise procedural pain in children. r, ScienceDirect, ResearchGate, PubMed, and Portal Garuda. The keywords used included “use of ice pack in preschool children”, “effectiveness of ice compress”, and “IV cannulation”. Of the 138 prospective articles identified, only 13 met the inclusion criteria. The quality of the articles was assessed using the 2020 CASP instrument. Results: Based on data extraction, the authors found that the use of ice packs is effective as a non-invasive intervention and can reduce pain during IV insertion. Conclusion: Paediatric nurses are advised to consider the use of ice packs as part of atraumatic care in order to minimise procedural pain in children.